Transmission processes of religious knowledge and ritual practice in Alevism between innovation and reconstruction - Zimmermann, Johannes; Karolewski, Janina; Langer, Robert (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2019)
Knowledge transmission in Alevism – Ritual practice – Written tradition – Oral lore – Scripturalisation – Memory and commemoration – Manuscripts – New media – Mimetics and imitation – Poet-minstrels – Gender roles – Transnational space – Yezidism.
Keywords: Konferenzschrift; Aleviten; Türkei; Innovation; Tradition; Religiöses Leben; Ritus